2018
DOI: 10.1039/c8ra07566b
|View full text |Cite
|
Sign up to set email alerts
|

An energy self-compensating phosphosilicate material applied to temperature sensors

Abstract: For years, researchers have been exploring effective methods of sustaining the emission intensity of phosphors with increasing temperature by suppressing emission loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Å Previous studies found that the large atoms usually occupy C1-C3 sites or sometimes C1, C2, and C5 while small cation ions can fill C4 and C5 sites [51][52][53][54]. In the present work, the smaller ionic radius of Cr 3+ (0.76 Å) suggests that it will fill C4 and C5 sites, expand or shrink the crystal structure, effectively replace some Ca 2+ sites, and prevent the formation of other phases.…”
Section: Xrd Profile and Tem Images Analysismentioning
confidence: 46%
“…Å Previous studies found that the large atoms usually occupy C1-C3 sites or sometimes C1, C2, and C5 while small cation ions can fill C4 and C5 sites [51][52][53][54]. In the present work, the smaller ionic radius of Cr 3+ (0.76 Å) suggests that it will fill C4 and C5 sites, expand or shrink the crystal structure, effectively replace some Ca 2+ sites, and prevent the formation of other phases.…”
Section: Xrd Profile and Tem Images Analysismentioning
confidence: 46%